Women Behind Rubber Sap : Gender Struggle in Plantations East Sumatra during the Colonial Period - Lukitaningsih (HUMANISMA : Journal of Gender Studies, 2025)
The development of rubber plantations in East Sumatra during the colonial period absorbed a lot of workers, including women. In an unequal work structure, women occupy the most vulnerable positions. This study aims to analyze the experience, gender inequality, and survival strategies of women workers in rubber plantations during the colonial period. The methods used are historical methods, including heuristics, source criticism, interpretation, and historiography. Data sources come from colonial archives such as Memorie van Overgave, Staatsblad van Nederlandsch-Indie, Algeemene Secretarie, Koloniale Verslag, and newspapers. The study highlights the injustices experienced by women workers, such as low wages, long working hours, separation from family, sexual exploitation, and harsh punishment. Gender inequality is not only evident in the division of labor, but also from the systemic exploitative practices hidden behind the productivity narrative. These findings show that gender-based power relations formed the face of injustice in East Sumatra rubber plantations during the colonial period. Through the Women Behind Rubber case study, this research offers a new perpective on gender dynamics in an exploiative economic and political context.The main contribution of this research is its ability to connect past hstory with contempory issues related to gender equality and workers rights.Its implications are highly relevant to our current efforts in addressing gender inequality in modern industrial sector, as well as promoting more inclusive and pro-women policies.